Analysis of Intellectual Property Rights as Collateral in Government Regulation No. 24/2022 - Nurdiansah, Muhamad Andre; Revendy, Evan Rayhan; Bil Haqi, Ahmad Nathique (Westscience Press, 2025)
The rapid development of Intellectual Property Rights (IPR) is closely linked to advances in technology, information, and communication. The existence of IPR enhances the quality of produced goods, thereby supporting economic growth. To foster the development of the creative economy in Indonesia, Law No. 24 of 2019 on the Creative Economy was enacted, with its implementation further regulated under Government Regulation No. 24 of 2022, which, among other provisions, addresses financing schemes. Using a normative juridical research method with a statutory approach, the findings reveal that IPR asset valuation can be conducted through the Cost-Based Approach, Market-Based Approach, Income-Based Approach, and other valuation methods, in accordance with applicable valuation standards. Regarding legal protection for creditors, the Consumer Protection Law applies.